From nutritional profiles to digestibility insights: exploring palm kernel cake and decanter cake in broiler diets - Azizi, Mohammad Naeem; Loh, Teck Chwen; Chung, Eric Lim Teik; Ab Aziz, Muhamad Faris; Foo, Hooi Ling; Liu, Jiaxiang; Aiman Farzana, Zakaria; Samuel Raj, Letchumanan (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
This study aimed to evaluate the composition of palm kernel cake (PKC) and decanter cake (DC) and assess their nutrient digestibility in broilers. One hundred one-day-old male broiler chicks (Ross 308) were divided into two dietary treatment groups. The diets were 90.3% PKC- and DC-based and contained 0.3% titanium dioxide (TiO2) as an indigestible marker. The data were analyzed using the Statistical Analyses System (SAS). Treatment means were compared using a two-sample t-test at a 5% significance level. This study found that PKC had a higher (p < 0.05) crude protein (CP) content (18.19%) and lower (p < 0.05) ether extract (EE) content (9.33%) compared to DC (16.47% CP, 11.17% EE). Additionally, DC contained a higher (p < 0.05) ash, crude fiber (CF), and gross energy (GE) content. Both PKC and DC had the highest standard ileal digestibility (SID) for energy (EE), with PKC showing a higher SID (p < 0.05) for CP and EE compared to DC. The apparent metabolizable energy (AME) values were 2079.47 kcal/kg for PKC and 2011 kcal/kg for DC, with no significant differences (p > 0.05) between these by-products. Furthermore, glutamic acid was the most abundant amino acid (AA) in both PKC (45.12 g/kg) and DC (25.59 g/kg). Additionally, PKC had higher (p < 0.05) SID values for methionine (58.58%) and arginine (64.84%) compared to DC (33.15% and 14.09%), with arginine showing the highest SID in PKC (64.84%) and alanine in DC (46.48%).